Digital exhaustion of the right of distribution in the European Union copyright law - Drakšas, Justinas (Vilnius University Open Series, 2023)
In this article, the author presents the conditions for exhaustion of the distribution right and overviews the main sources regulating exhaustion, from which the main problem related to the recognition of digital exhaustion of the distribution right - the separation of the right of communication to the public and the right of distribution - arises. In the view of the author, transmission of works or objects of related rights over computer networks for permanent use by its users is not fully attributable to distribution, due to international and EU provisions restricting the distribution right to material copies only. Therefore, the author considers that intervention of the legislator is necessary in order to implement the rule of digital exhaustion and to make a clear distinction between the rights of distribution and communication to the public. Other risks associated with the digital exhaustion of the distribution right, such as the “first copy” problem, and the inefficiency of the technical measures to ensure that works (other objects) transmitted over computer networks are not reproduced without the permission of the rightholder, are also analysed in this work. Notwithstanding the mentioned concerns, the author suggests reviewing legal provisions related to digital exhaustion in order to ensure that copyright law better meets actual social relationships and key consumer needs.
Keywords: digital exhaustion of the distribution right; copyright law; computer networks; communication to the public right; sale and licensing of digital works